High Quality Power Supply Service Mode Considering Service Life of Mitigation Equipment Against Voltage Sag - Pei LI; Yongjun YU; Zhiquan MA; Chongkai CAI (Zhongguo dianli)
The voltage sag mitigation equipment has such problems as large one-time investment cost and high investment threshold, which urgently need to be solved through a new high quality power supply service mode. Therefore, a high quality power supply mode considering the service life of mitigation equipment against voltage sag (HPSL) is proposed. Firstly, a HPSL operation mode is proposed and the operation entities and service process of HPSL are defined. And it is proposed that the old equipment shall participate in the mitigation management if they can meet the user's needs. Secondly, a HPSL service pricing optimization model is established with a comprehensive consideration of the cost and income composition of equipment manufacturers and users, and with the maximum net income of both parties as objective. Furthermore, a service fee game model is established based on the Stackelberg game. The model takes the adjustment of additional income coefficient by equipment manufacturers as the decision-making, and the adjustment of service duration by users as the response, which is in line with the actual situation. The improved genetic algorithm is used to solve the model. Finally, a case study is conducted by taking a large film factory as an example. It is proved that the proposed mode can reduce the governance cost of users, and improve the service fee income of equipment manufacturers.